Synthesizing a High Gain Planar Array Antenna for Volume Scanning Arrays - Tokan, Fikret; Gunes, Filiz (ELECTROMAGNETICS ACAD, 2011)
In this work, a rectangular planar array antenna which can scan 0 degrees <= theta <= 60 degrees region in phi = 0 degrees principal plane is synthesized to be used in volume scanning radars. Radiation patterns of each linear array constituting the rectangular planar array are steered to the determined directions in order to generate a super positioned 60 degrees width radiation pattern. In this process, rectangular patch antennas are utilized in each of these linear antenna arrays. The radiation pattern designed for volume scanning in the desired region is verified by using FEKO, full-wave simulation software.
Keywords: Engineering; Physics